Особливості виникнення інтелектуально-університетської комунікації Середньовіччя - Казакова, Т.В. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2007)
В статье предложена концепция «идеи университета» как канала социальной коммуникации средневековой Западной Европы. Выявлены две главные причины его зарождения. The article introduces the conception of "the idea of the university" as a social communication channel in the medieval Western Europe. Two main reasons of its origin are revealed.
Keywords: університет; університетська комунікація; Середньовіччя